17.7k views
21 votes
Hep asappppppppppppp

Hep asappppppppppppp-example-1
User Ajmicek
by
4.3k points

1 Answer

4 votes

Answer:

(6 , -1)

Explanation:

2x+ y = 11 ----------------(I)

y = 11 - 2x --------------------(II)


(1)/(2)x - 5y = 8

Multiply the whole equation by 2


2*(1)/(2)x -2*5y = 2*8

x - 10y = 16 --------------------(III)

Substitute y = 11- 2x in equation (III)

x - 10(11 - 2x) = 16

x - 110 + 20x = 16

21x - 110 = 16

21x = 16 +110

21x = 126

x = 126/21

x = 6

Plugin x = 6 in equation (II)

y = 11 - 2*6

y = 11 - 12

y = -1

User Logikal
by
5.1k points